Gobiid fishes of the genus Bryaninops from the Red Sea, with description of two new species and two new records - Suzuki, Toshiyuki; Bogorodsky, Sergey V.; Randall, John E. (Zootaxa, 2012)
Three species of the gobiid fish genus Bryaninops were previously known for the Red Sea: B. natans, B. ridens, and B.yongei. Two new species are described, B. discus, similar to B. loki, differing in coloration and in having dish-like insteadof cup-like pelvic fins in adults; and B. spongicolus, closely related to B. dianneae from Fiji, distinct in having shorterpelvic fins, a rounded instead of truncate caudal fin, and differences in life color. Bryaninops loki and B. tigris are reportedas first records for the Red Sea, the former from a specimen from Sudan and an underwater photo from the Sinai Peninsula, the latter from an underwater photo taken off Egypt.